2004
DOI: 10.2465/jmps.99.104
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenesis of Ashigawa and Tonogi granitic intrusions, southern part of the Miocene Kofu Granitic Complex, central Japan: M-type granite in the Izu arc collision zone

Abstract: The Ashigawa and the Tonogi intrusions comprise the southern part of the Miocene Kofu Granitic Complex (KGC), which is the largest pluton exposed in the Izu collision zone. The Ashigawa intrusion mainly consists of tonalite and subordinate amounts of trondhjemite, and the Tonogi intrusion is predominantly composed of tonalite. The rocks in both intrusions are classified as M type granite. These are characterized by relatively low K 2 O (<1.9 wt.%) and Rb (<48 ppm) and LREE enriched chondrite normalized REE pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
1
19
0
1
Order By: Relevance
“…They are composed of various types of granitoids including tonalite, trondhjemite, granodiorite, monzogranite, and granite (e.g., Takahashi 1989;Sato 1991;Saito et al 2007b). Recent petrogenetic investigations of the Tanzawa plutonic complex and Kofu granitic complex have shed new light on the deep crustal processes beneath the collision zone (e.g., Kawate and Arima 1998;Saito et al 2004Saito et al , 2007a. Kawate and Arima (1998) suggested that the tonalitic Tanzawa plutonic complex (Fig.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…They are composed of various types of granitoids including tonalite, trondhjemite, granodiorite, monzogranite, and granite (e.g., Takahashi 1989;Sato 1991;Saito et al 2007b). Recent petrogenetic investigations of the Tanzawa plutonic complex and Kofu granitic complex have shed new light on the deep crustal processes beneath the collision zone (e.g., Kawate and Arima 1998;Saito et al 2004Saito et al , 2007a. Kawate and Arima (1998) suggested that the tonalitic Tanzawa plutonic complex (Fig.…”
mentioning
confidence: 98%
“…Note the northward convex structure of Median Tectonic Line in central Japan (Kanto Syntaxis). Light solid lines outline seamounts shallower than 2,000 m. b Geological map of the Izu Collision Zone (modified after Takahashi and Saito 1997;Saito et al 2004Saito et al , 2007b. ISTL ItoigawaShizuoka Tectonic Line, BTL Butsuzo Tectonic Line, TATL Tonoki-Aikawa Tectonic Line, KF Kannawa Fault, KO Koma terrane, MI Misaka terrane, TA Tanzawa terrane, IZ Izu terrane.…”
mentioning
confidence: 99%
“…SiO 2 versus SrI (at zircon U Pb age) of the rocks of the Tanzawa plutonic complex (Kawate, 1996) (a), the Kofu granitic complex (b), and the Kaikomagatake pluton (c). The compositionalˆeld of Izu Bonin arc basaltic rocks (Taylor and Nesbitt, 1998;Hochstaedter et al, 2001) and Shimanto metasedimentary rocks in the Izu Collision Zone (Saito et al, 2004(Saito et al, , 2007a(Saito et al, , 2007b are also shown for comparison.…”
Section: 齊藤mentioning
confidence: 99%
“…Petrogenesis of the Izu Collision Zone granitoid plutons together with other oceanic arc collision related magmatism collectively suggest that collision has played an important role in transforming juvenile oceanic arc into mature continental crust. Takahashi and Saito, 1997;Saito et al, 2004Saito et al, , 2007aSaito et al, , 2007bSaito et al, , 2012 (Condie, 1993;Gao et al, 1998;Borodin, 1998;Wedepohl, 1995;Rudnick and Gao, 2003) . SiO 2 versus SrI (at zircon U Pb age) of the rocks of the Tanzawa plutonic complex (Kawate, 1996) (a), the Kofu granitic complex (b), and the Kaikomagatake pluton (c).…”
Section: 齊藤mentioning
confidence: 99%
See 1 more Smart Citation